Bioluminescence Imaging-Based Assessment of the Anti-Triple-Negative Breast Cancer and NF-Kappa B Pathway Inhibition Activity of Britanin - Xu, Xinyi; Guo, Yingying; Du, Getao; Liu, Huifang; Wang, Lin; Chen, Dan (Frontiers in Pharmacology, 2020)
Britanin has been reported to have therapeutic effects on neurodegenerative and inflammation-based diseases. However, whether it is involved in the regulation of triple-negative breast cancer development has not been elucidated. In this study, we investigated the anti-tumor activity against triple-negative breast cancer tumor of Britanin by bioluminescence imaging in vivo using athymic (nu/nu) mice implanted with MDA-MB-231 and SUM-159 cells expressing a luciferase reporter gene, and explored the anti-tumor mechanism of Britanin. The results showed that Britanin treatment inhibited triple-negative breast cancer cell proliferation in vivo, and Cell Counting Kit-8 (IC50 values are 4.27 and 5.05 μM) and colony formation tests (P < 0.001) confirmed this result. Transwell assays were conducted to verify that Britanin treatment inhibited cell migration and invasion (P < 0.001). Apoptosis was determined by TdT-mediated dUTP nick-end labeling method. Western blot and qRT-PCR analysis showed that Britanin treatment caused a decrease in the member expression of NF-kappa B signaling pathway. Computational modeling showed that Britanin could directly bind to a p-65 core region composed of Cys38, Cys120, and Gln128 residues. The results showed that the inhibitory mechanisms of Britanin on cancer cells may be by ways of inhibiting the NF-kappa B pathway. In addition, bioluminescence imaging screening system is useful for accelerating the application of Britanin in the antitumor field, and provides a useful tool for evaluating the phytochemicals efficacy in inhibiting cancer cell proliferation in animal models.